2013
DOI: 10.1097/jcp.0b013e31828f5a7a
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, Pharmacokinetics, and Pharmacodynamics of Single-Dose Almorexant, an Orexin Receptor Antagonist, in Healthy Elderly Subjects

Abstract: Sleep disorders are common in the elderly population. Orexin receptor antagonism has been proposed as a new sleep-enabling approach to treat insomnia. The tolerability, pharmacokinetics, and pharmacodynamics of ascending single doses of almorexant, a dual orexin receptor antagonist, were investigated in healthy elderly male and female subjects. In this double-blind, placebo- and active-controlled study, each dose (100, 200, and 400 mg) was investigated in a separate group of 12 subjects (almorexant, placebo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Orexin antagonist effects on sleep architecture appear to be more idiosyncratic, with Suvorexant increasing REM sleep [187] while Actelion recently reported a DORA which increases NREM sleep in rats [188]. The hypnotic effects of orexin antagonists raises the possibility of cognitive impairment and some memory impairments have been observed in elderly patients given Almorexant [186]. However, studies on cognitive effects in rats have shown that DORAs have a relatively greater therapeutic window than current treatments for insomnia [189].…”
Section: Potential Side Effects and Safetymentioning
confidence: 94%
See 1 more Smart Citation
“…Orexin antagonist effects on sleep architecture appear to be more idiosyncratic, with Suvorexant increasing REM sleep [187] while Actelion recently reported a DORA which increases NREM sleep in rats [188]. The hypnotic effects of orexin antagonists raises the possibility of cognitive impairment and some memory impairments have been observed in elderly patients given Almorexant [186]. However, studies on cognitive effects in rats have shown that DORAs have a relatively greater therapeutic window than current treatments for insomnia [189].…”
Section: Potential Side Effects and Safetymentioning
confidence: 94%
“…Animal studies have shown the importance of orexins for feeding [13,180], motivation [181], sleep/ wakefulness [182,183], male sexual behavior [98] and female proestrus [184] which raises the possibility of side effects such as anorexia, weight loss, anhedonia, and asexuality in addition to observed side effects such as somnolence, fatigue and muscle weakness [58,60,63,79,80,185,186]. Orexin antagonist effects on sleep architecture appear to be more idiosyncratic, with Suvorexant increasing REM sleep [187] while Actelion recently reported a DORA which increases NREM sleep in rats [188].…”
Section: Potential Side Effects and Safetymentioning
confidence: 99%
“…Interestingly, OXA was also detected in the areas surrounding the CP blood capillaries, suggesting that OXA levels in the CSF are probably regulated by CP activity (Tafuri et al, 2009). Several OXR antagonists effectively induce sleep in volunteers and insomnia patients (Equihua et al, 2013;Hoyer and Jacobson, 2013;Hoever et al, 2010Hoever et al, , 2012Hoever et al, , 2013Brisbare-Roch et al, 2007;Aissaoui et al, 2008). The development of these agents may lead to novel therapies for insomnia without the side effect profile of hypnotics, such as impaired cognition, disturbed arousal, and motor balance difficulties (Equihua et al, 2013).…”
Section: Sleep and Sleep Disordersmentioning
confidence: 95%
“…The pharmacokinetic profile of Almorexant is characterized by rapidly decreasing concentrations to approximately 20% of the maximum concentration over 8 hours, with a terminal half-life of 32 hours in humans (Hoever et al, 2013). In male canines, oral administration of Almorexant at a dose of 100 mg×kg 21 induced clinical signs of somnolence for up to Prolonged Sympathoexcitation by Repetitive Orexin-A 6 hours (Brisbare-Roch et al, 2007).…”
Section: Discussionmentioning
confidence: 99%